Differences in Behavior Preventing Smoking (Reviewed Based on Planning Behavior Theories) between Before and After Intervention with Jigsaw Technique - Toghur Arifani Lubis; R. Kintoko Rochadi; Namora Lumongga Lubis (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Various interventions to prevent smoking at this time have been carried out on modifications of peer influence, not only to improve their knowledge, adolescents need to be given skills to control themselves, especially from peer influences with the aim that smoking is not socially accepted for adolescents and cooperative learning is a suitable method. Cooperative learning is successfully used by teachers and researchers at various levels of education, the field of health, especially public health education, and is proven effective when someone teaches his peers about health. This study uses a cooperative learning model with a jigsaw technique, aimed at analyzing differences in smoking prevention behavior (based on planned behavior theory consisting of attitudes, subjective norms, behavioral control, and intentions) between before and after the intervention. Research with quasi experiment type has been carried out in MTS Amin Darussalam of 20 students who were collected by purposive sampling technique, data were collected by questionnaire and analyzed by Chi-Square. The results showed that there were differences in attitudes, subjective norms, PBC and intentions between before and after the intervention with jigsaw.